A High Resolution Molecular Atlas of the Fetal Mouse Lower Urogenital Tract - Abler, Lisa L. (2011)
Epithelial-stromal interactions in the lower urogenital tract (LUT) are integral to prostatic and seminal vesicle development in males, vaginal and uterine development in females, and urethral development in both sexes. Gene expression profiling of isolated LUT stroma and epithelium has unraveled mechanisms of LUT development, but such studies are confounded by heterogeneous and ill-defined cell sub-populations contained within each tissue compartment. We used in situ hybridization to synthesize a high-resolution molecular atlas of 17 days post coitus fetal mouse LUT. We identified mRNAs that mark selective cell populations of the seminal vesicle, ejaculatory duct, prostate, urethra and vagina, subdividing these tissues into 16 stromal and 8 epithelial sub-compartments. These results provide a powerful tool for mapping LUT gene expression patterns and also reveal previously uncharacterized sub-compartments that may play mechanistic roles in LUT development of which we were previously unaware.